Evaluation of Endemic Status of Lymphatic Filariasis in Areas Adjoining to the Endemic District of Bangladesh (Bangladesh Medical Journal, 2019)
In Bangladesh, it was assumed that the endemicity of Lymphatic Filariasis (LF) in areas adjoining to the endemic districts may be related to the endemicity of this districts due to presence of sufficient vectors and extend of microfilaria for it’s chronicity. LF is caused by nematodes (round worms) and mainly transmitted to man by the infected- Culex mosquito. Among the 3 types of thread-like filarial worms; Wuchereria bancrofti is responsible for 90% of the cases. Filariasis is endemic in 34 districts and clinical cases are reported from 51 districts, with high endemicity in the northern part of Bangladesh. This cross-sectional survey study was conducted among 6,100 participants at areas adjoining to the endemic districts of LF to evaluate the endemic status during the period of 1st July 2014 to 30th June 2016. Total 10 sub-districts (upa-zilas) were selected from 5 districts of 4 divisions adjoining to the filaria endemic districts, and then 02 sub-districts (Sub-D) from each district. From each Sub-D, 02 unions (several unions constitute a sub-districts) and 10 ‘spot check site (SCS)’ from these unions were selected randomly. Villages and nearby areas of the ‘SCS’ were publicized previous day of data collection by personnel from Upa-zila Health Complexes (UHC) and audio announce. Average 60 samples were collected from each ‘SCS’ and interviewed participants in the same day. Data were collected by using On Site Filariasis Rapid test cassette for identifying the filarial cases and socioeconomic and demographic data had also been collected by interviewing using questionnaire. The mean age of the participants was 30.03+14.85; female - male ratio of were 1: 0.97 and almost equal numbers (20%-30%) respondents were in each age group (5-15, 16-25, 26-40 and >40 years). Most of the participants were Muslims and two third were married, where 56% were completed primary education or could not read and write and 44% secondary level or above. Nearly three fourth of participants were involved in household/ agricultural works or laborers; others were students, had service and small business and 01% had no work. Two third of participants had no income or could not state and other had monthly income ranges from 1000 to 10,000 taka. Prevalence rate of LF test positive cases was 0.2%; male-female ratio was 1:3, IgG was detected in 83% and rest IgM. Two third of cases were in age group 16-25 years and one fourth in >40 years; only 8.3% were in 5-15 years and no cases were found in age group 26-40 years. All positive cases were Muslim and two third were married, where majority were illiterate or primary and rest of them completed secondary or above. Two third of cases did household or agricultural works and rest were students. Two third had no income or could not state, one fourth had >2000 to 5000 taka and only 8.3% had income 5001–>10000 taka. The highest prevalence rate (2.50/1000 Pop) were found in Naogaon & Gaibandha districts and sub-districts were Niamotpur & Sadullapur (5.0/1000 Pop) and no cases were detected at Singra (Natore), Porsha (Naogaon), Palashbari (Gaibandha). Two third of cases suffered from itching; majority had fever and cough and one third stated breathlessness. Clinical signs edema was seen in feet 41.7% of cases. Few cases 08.3% had reached to health care facilities and 91.7% cases had never sought diagnostic facilities. Adjoining areas of endemic districts of LF are prone to spread this disease. Routine survey of LF cases would be continued in areas adjoining to the endemic district.Bangladesh Med J. 2019 May; 48 (2): 13-19